2019
DOI: 10.1101/654228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity-induced gut microbiota dysbiosis can be ameliorated by fecal microbiota transplantation: a multiomics approach

Abstract: 2 18 Abstract 19 Obesity and its comorbidities are currently considered an epidemic, and the involved 20 pathophysiology is well studied. Recently, the gut microbiota has emerged as a new potential 21 therapeutic target for the treatment of obesity. Diet and antibiotics are known to play crucial 22 roles in changes in the microbiota ecosystem and the disruption of its balance; therefore, the 23 manipulation of gut microbiota may represent a strategy for obesity treatment. Fecal microbiota 24 transplantation, d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Currently, FMT has been clinically shown to be effective for treating intestinal diseases, such as Clostridium difficile infection and inflammatory bowel disease. 121 Some parenteral diseases are also being explored, such as autism, 122 obesity, 123 and type 2 diabetes. 124 Vrieze et al 125 performed FMT treatment on patients with metabolic syndrome, and the result indicated that patients receiving gut flora from leptin donor displayed improved insulin sensitivity and increased butyrate production.…”
Section: Tang Et Al (2013) 133mentioning
confidence: 99%
“…Currently, FMT has been clinically shown to be effective for treating intestinal diseases, such as Clostridium difficile infection and inflammatory bowel disease. 121 Some parenteral diseases are also being explored, such as autism, 122 obesity, 123 and type 2 diabetes. 124 Vrieze et al 125 performed FMT treatment on patients with metabolic syndrome, and the result indicated that patients receiving gut flora from leptin donor displayed improved insulin sensitivity and increased butyrate production.…”
Section: Tang Et Al (2013) 133mentioning
confidence: 99%
“…In the current study, we sought to understand whether normalizing gut microbiota composition in HF fed obese animals would offset the detrimental physiological effects of consuming an energy dense, high in fat and sugar, diet. Prior reports (40,55), have shown that preventing dysbiosis in HF fed animals improves metabolic outcomes. Most of these interventions were started at the same time as HF diet introduction.…”
Section: Discussionmentioning
confidence: 96%
“…Recent advances in our knowledge of host-associated microbiomes have made it clear that these communities are crucial to maintain their host's health. Changes in the community structure of a microbiome can result in a disease-associated state known as "dysbiosis" (Guirro et al, 2019;Sobhani et al, 2019;Tanja Dapa et al, 2022). It has also been shown that some human gut commensal bacteria perform deleterious functions, contributing to disease (Rath et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy provides a targeted approach, resulting in species-or gene-specific manipulation, which can lead to detectable mechanistic and ecological effects. This lies in contrast to broad methods of microbiome manipulation, such as the use of prebiotics (Enam and Mansell, 2019), use of probiotics (Mao et al, 2018), and fecal microbiota transplant (FMT) (Guirro et al, 2019), which produce global effects in the community whose outcomes might be hard to predict. Additionally, since plasmid transfer has been observed across phyla (Klümper et al, 2015) and even across domains (Bates et al, 1998), conjugation has the potential to deliver DNA to a wide variety of hosts.…”
Section: Introductionmentioning
confidence: 99%